Bioavailability and remineralization rates of sediment-derived dissolved organic carbon from a Baltic Sea depositional area - Lengier, Monika; Koziorowska-Makuch, Katarzyna; Szymczycha, Beata; Kuliński, Karol (Frontiers in Marine Science, 2024)
This pilot study investigated the bioavailability and remineralization kinetics of the sediment-derived dissolved organic carbon (DOC) from the Gdańsk Deep, a depositional area in the Baltic Sea. This was assessed in the long-lasting (126 d) incubation experiment, in which the mixture of DOC from sediment pore water and bottom water was exposed to oxic microbial respiration with incubation of bottom water as a control run. The obtained decay curves allowed us to distinguish three DOC fractions: labile (DOCL), semi-labile (DOCSL), and refractory (DOCR). In bottom water, the refractory fraction was predominant and amounted to almost 85% of total DOC, whereas about 15% of DOC was bioavailable: 6% labile and 9% semi-labile. In contrast, DOC from pore water was much more bioavailable DOC ( 55% of total DOC) and contained 11% DOCL and 44% DOCSL. The remineralization rate constants recalculated to the in situ temperature of 6°C for labile and semi-labile DOC in pore water were 0.025 d−1 and 0.002 d−1, respectively, whereas, in bottom water, 0.026 d−1 and 0.004 d−1. The half-life times for DOCL were comparable for both bottom water and pore water and amounted to 26.2 d and 27.6 d, respectively. For DOCSL, the half-life time was shorter for bottom water (165.5 d) than for pore water (322.9 d).